Remember to use PEMDAS when solving.
= 7 + (5 – 9)2 + 3(16 ÷ 8)
= 7 + (-4)2 + 3(2)
= 7 + (-8) + 6
= -1 + 6
= 5
Best of Luck!
Answer:
Step-by-step explanation:
a I’m pretty sure
Step-by-step explanation:
4x +13 +79+79+ 11x-6 = 360
15x +165 = 360
15x = 195
x =13
QRS = 11(13)-6 = 137
Answer:
r = 21
Step-by-step explanation:
nth of sequence P :

: 
Answer:

Step-by-step explanation:
<u>The Derivative of a Function</u>
The derivative of f, also known as the instantaneous rate of change, or the slope of the tangent line to the graph of f, can be computed by the definition formula

There are tables where the derivative of all known functions are provided for an easy calculation of specific functions.
The derivative of the inverse tangent is given as

Where u is a function of x as provided:

If we set

Then


Taking the derivative of y
![y'=3[tan^{-1}(x+\sqrt{1+x^2})]'](https://tex.z-dn.net/?f=y%27%3D3%5Btan%5E%7B-1%7D%28x%2B%5Csqrt%7B1%2Bx%5E2%7D%29%5D%27)
Using the change of variables
![\displaystyle y'=3[tan^{-1}u]'=3\frac{u'}{1+u^2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%27%3D3%5Btan%5E%7B-1%7Du%5D%27%3D3%5Cfrac%7Bu%27%7D%7B1%2Bu%5E2%7D)

Operating

